Potential role of microbiome in oncogenesis, outcome prediction and therapeutic targeting for head and neck cancer. (December 2019) - Orlandi, Ester; Iacovelli, Nicola Alessandro; Tombolini, Vincenzo; Rancati, Tiziana; Polimeni, Antonella; De Cecco, Loris; Valdagni, Riccardo; De Felice, Francesca
Highlights: The role of oral/laryngeal microbioma on HNC carcinogenesis needs investigation. Oral microbiota change during RT is associated to oropharyngeal mucositis progression. Clinical trials testing the value of microbiota in HNC treatment response are needed. Microbiota can be a target for probiotics in order to modulate RT-related toxicity. Abstract: In the last decade, human microbiome research is rapidly growing involving several fields of clinical medicine and population health. Although the microbiome seems to be linked to all sorts of diseases, cancer has the biggest potential to be investigated. Following the publication of the National Institute of Health - Human Microbiome Project (NIH-HMP), the link between Head and Neck Cancer (HNC) and microbiome seems to be a fast-moving field in research area. However, robust evidence-based literature is still quite scarce. Nevertheless the relationship between oral microbiome and HNC could have important consequences for prevention and early detection of this type of tumors. The aims of the present review are: (i) to discuss current pre-clinical evidence of a role of oral microbiome in HNC; (ii) to report recent developments in understanding the human microbiome's relationship with HNC oncogenesis; (iii) to explore the issue of treatment response and treatment toxicity; (iv) to describe the role of microbiota as potentially modifiable factor suitable for targeting by therapeutics. Further studies are needed to better establish the causal relationship between oral microbiome and HNC oncogenesis. Future trials should continue to explore oral microbiome in order to build the scientific and clinical rationale of HNC preventative and ameliorate treatment outcome.